RENANG SEBAGAI AKTIVITAS FISIK PREVENTIF DALAM MENINGKATKAN KESEHATAN FISIK DAN MENTAL - Tamba G, Kuntum; Nasution, Diyah Salsabil; Mutia; Suprayitno; Ahady, Mohammad Yan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low levels of physical activity have become one of the major health challenges in modern society and contribute to the increasing prevalence of non-communicable diseases and psychological disorders. Preventive physical activities are therefore needed to improve overall health and quality of life. Swimming is considered one of the most effective forms of exercise because it involves almost all body muscles while minimizing the risk of joint injury. This study aims to analyze the role of swimming as a preventive physical activity in improving physical and mental health. The research employed a qualitative descriptive method through a literature review by examining various scientific publications related to swimming and health published between 2010 and 2025. The findings indicate that swimming provides significant benefits for cardiovascular fitness, respiratory function, muscle strength, body metabolism, stress reduction, emotional stability, and sleep quality. In addition, swimming is suitable for various age groups and individuals with specific health conditions because of its low-impact characteristics. Therefore, swimming can be regarded as an effective preventive exercise in supporting physical and mental well-being.